Pancasila: Cinta Kasih Yang Mempersatukan - Moses William Yuwono (Parahyangan Catholic University, 2020)
Recent cases of discrimination and intolerance have threatened the unity of Indonesia. We may forget that the unity in diversity (Bhineka Tunggal Ika) is a ‘given’ thing for the inhabitants of Indonesia. This article is a descriptive-critical reflection to this given-unity-in-diversity in the light of Pancasila as the practical-philosophy of Indonesian people. In the face of Indonesian people’s ethnicity, race, and religion diversities, a unifying love is needed, which is none other than the Pancasila itself.